1994
DOI: 10.1002/ana.410360504
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of acetylcholine receptor: Effects on experimental myasthenia gravis

Abstract: The abnormality in myasthenia gravis (MG) is a deficiency of acetylcholine receptors (AChRs) at neuromuscular junctions due to an antibody-mediated autoimmune attack. Although immunosuppressive drugs are usually beneficial in MG, they produce generalized suppression of the immune system. Treatment should specifically inhibit the immune response to AChR. Oral administration of an antigen may induce specific tolerance and has recently been tested for treatment of several cell-mediated experimental and human auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(56 citation statements)
references
References 39 publications
2
53
0
1
Order By: Relevance
“…In this regard, a gradient of sensitivity to tolerance induction with Thi > Th2 > B cells has been described recently [26]. Feeding Torpedo AChR induced tolerance in EAMG, in which the clinically relevant autoantibody (anti-rat AChR) was more inhibited than antiTorpedo AChR antibody [35]. In the present study, even the autoantibody was not suppressed in the thymically tolerized rats.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In this regard, a gradient of sensitivity to tolerance induction with Thi > Th2 > B cells has been described recently [26]. Feeding Torpedo AChR induced tolerance in EAMG, in which the clinically relevant autoantibody (anti-rat AChR) was more inhibited than antiTorpedo AChR antibody [35]. In the present study, even the autoantibody was not suppressed in the thymically tolerized rats.…”
Section: Discussionsupporting
confidence: 66%
“…Our test on the elTect of intrathymic injection of AChR 7 days before active immunization resulted in a failure of inhibition of antibody production. Such results may be in part due lo the striking immunogenicity or insolubility of AChR [33][34][35]. Alternatively, the dosage of AChR may have been too small to induct!…”
Section: Discussionmentioning
confidence: 99%
“…T helper 1 cytokines IFN-␥ and IL-2 have been shown to be involved in the pathogenesis of experimental autoimmune MG (28,29). To test the effect of the dual APL on the p195-212-specific T cells, cells of the line were incubated with p195-212 with or without the dual or reversed dual APL for 24 (IFN-␥, IL-2, and IL-10) or 48 (TGF-␤) h. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most significant effects of the dual APL on the cytokine balance was the up-regulation of TGF-␤. It was demonstrated that secretion of TGF-␤ was up-regulated (in parallel to down-regulation of IFN-␥ secretion) in mice and rats after oral or nasal administration of AChR, and that correlated with an improvement in their clinical status (55)(56)(57)(58). Furthermore, a correlation was found between clinical remission and increase in TGF-␤ expression in mononuclear cells of MG patients (59).…”
Section: Immunomodulation Of Cytokines By the Dual Aplmentioning
confidence: 95%